Ensino superior para surdos: o processo educacional na ótica dos estudos culturais - Silva, Polliana Barboza da (2018)
Research developed in the light of Cultural Studies of Education and based on Deaf Studies comprises deaf people as beings who have identities, culture, ways of life, experiences and organizations. This condition is represented, primarily, by the existence of sign language as a factor of development and communication. In the case of Brazil, Libras (Brazilian Sign Language) is recognized as the first language of deaf people. Taking into account this linguistic-cultural panorama, the present study was developed with the purpose of analyzing the narratives and the pedagogical practice that involved three deaf students, three female teachers and one male teacher in the educational process of deaf students, developed in an institution of technical, technological and higher education, in the undergraduate courses in Industrial Automation, Interior Design and Chemistry, located in the city of João Pessoa / PB. The data, obtained through interviews and observations were analyzed, based on Cultural Studies and Deaf Studies, focusing on the categories: interviewees' data, communicative process, classroom participation, teaching strategies, teaching experiences and students in primary and higher education, the relation and communication with the interpreters of Libras and the expectations of improvements in the educational process of the deaf students. Based on my hypothesis, based on my practice and the poststructuralist conception of curriculum, that undergraduate courses lack the knowledge and skills to develop an adequate educational process with deaf students. The results pointed to the urgent need for deaf identities to be considered in the educational process, given that pedagogical actions are based on the listener culture. The main indication of this is the communicative limitations between teachers and deaf students, due to the fact that teachers do not know Libras. The data also pointed out that it is necessary to re-significate the teaching strategies, in order to consider deaf students. This fact was even explained by a teacher who in her narrative mentioned the importance of the visual aspects and, in her pedagogical practice, developed dialogues in the classroom based on the visual resources, always asking questions and instigating the deaf student. In general, educational experiences, according to deaf students, were precarious, without adequate adaptation of materials, classes were less dynamic and with restricted use of Libras. The relation with the interpreters was seen as a positive factor by all deaf students, which can be due to the fact that the interpreters have a closer contact with the deaf culture. In conclusion, the educational process of deaf students needs to contemplate their specificities through a bilingual educational process that involves theoretical-epistemological and practical aspects, such as teaching methods, strategies, learning process, evaluation, among others, intersected by social, political and pedagogical factors.